1997
DOI: 10.1046/j.1526-4610.1997.3705277.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Features of Chronic Daily Headache in a Headache Clinic

Abstract: Although chronic daily headache is regarded as a syndrome encountered in headache clinics, clinical characteristics have only rarely been studied and the condition has not been documented in Thailand. To investigate the prevalence as well as clinical features of chronic daily headache in Thai patients, 220 patients visiting Chulalongkorn Headache Clinic were examined. Sixty cases (27.3%) were diagnosed as suffering from chronic daily headache (male to female ratio, 1:5.7). The average age of these patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 11 publications
2
51
1
5
Order By: Relevance
“…Between 58% and 71% report difficulties with sleep [5,13]. This is interesting, as sleep disturbance has been noted as an aggravating factor for HAs [12,13].…”
Section: Psychological Factorsmentioning
confidence: 79%
See 2 more Smart Citations
“…Between 58% and 71% report difficulties with sleep [5,13]. This is interesting, as sleep disturbance has been noted as an aggravating factor for HAs [12,13].…”
Section: Psychological Factorsmentioning
confidence: 79%
“…Between 58% and 71% report difficulties with sleep [5,13]. This is interesting, as sleep disturbance has been noted as an aggravating factor for HAs [12,13]. Rothrock et al [10] observed that 57% of chronic daily HA sufferers experienced insomnia; however, they did not observe any significant differences in sleep disturbance between chronic daily HA patients as compared to those with episodic HAs.…”
Section: Psychological Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…105 Thirteen percent of adults (8 of 60) in another study, recalled onset of CDH in childhood. 106 These data suggest that CDH may not remit or may only improve partially in a clinically significant number of children; [104][105][106][107] therefore, those at high risk for chronicity (see above) should be targeted for early "aggressive" intervention. 104 Additionally, children with CDH should be followed into late adult life to better define long term outcome; data bases such as those used in Taiwan provide a model to achieve this end.…”
Section: Outcomementioning
confidence: 99%
“…Estes achados foram semelhantes aos de Solomon e col. 3 , que encontraram dor em peso ou pressão em 87% e pulsátil em 29% de sua amostra e aos de Srikiatkhachorn & Phanthumchinda 23 que observaram dor em peso ou pressão em 65% e pulsátil em 46,7% de sua série, mas diferentes dos descritos por Krymchantowski e col. 22 , que relataram dor em pressão em 36,2% e pulsátil em 37,2% de 215 pacientes estudados. A associação de dor em peso ou pressão e pulsátil foi observada em menos de 6% dos pacientes deste estudo e em 17,2% dos pacientes da série de Krymchantowski e col. 22 .…”
unclassified